Lactation performance of the White Fulani cattle in southern Nigeria - Mrode, Raphael A. (Springer, 1988)
Data on the lactation performance of White Fulani cattle in southern Nigeria were analysed. The first lactation yield over a mean lactation period of 230.68±2.25 days averaged 810.89±32.11 kg, while overall lactation averaged 1018.28±18.10 kg over a mean lactation period of 249.67±3.28 days. The year of calving was a significant source of variation in both first and overall lactation yields but season of calving had no significant effect on lactation yield. Lactation yield and length were positively correlated. Heritability of 0.26±0.06 and 0.51±0.05 were obtained for lactation yield and length respectively from half-sib analysis while the repeatability estimates were 0.32±0.04 and 0.21±0.04 respectively. There was little difference in performance of the White Fulani cattle under the humid conditions of southern Nigeria compared to the semi-arid conditions of the north.